(untitled) (Research, Society and Development, 2021)
Introduction: Moringa is a tropical plant belonging to the Moringaceae family and has little-known healing properties. Objective: to evaluate the effect of moringa oil (Moringa oleífera L.) on skin healing in rats (Rattus novergicus). Methodology: 45 wistar rats (Rattus norvegicus), three months old, were used, divided into three treatments: GCN (negative control group): application of non-ionic cream; GOM (moringa oil group): addition of 10% of moringa oil to the non-ionic cream; GCP (positive control group): application of cream based on 1% silver sulfadiazine. The rats suffered a 1.0 cm circular incision in the dorsocervical region and the wounds were treated with the creams. Results: The evolution of the healing process was observed and the diameter of the wounds was measured. On the 3rd, 7th and 14th day of the experiment, five animals from each group were sacrificed for macrophage, neovessel and fibroblast counting. The macrophage count showed an increase (p <0.05) after seven days of applying the creams in all treatments. Neovessels and fibroblasts did not increase (p> 0.05) after seven days of application of the creams in the GCN and GCP treatments compared to three days after the beginning of the applications, with an increase (p <0.05) being observed only in the GOM treatment. Conclusion: The evidence obtained showed that the topical application of cream plus 10% moringa oil on injured skin influenced cellular events, optimizing tissue repair and attenuating the inflammatory process.